2017
DOI: 10.1007/s40588-017-0069-3
|View full text |Cite
|
Sign up to set email alerts
|

JC Polyomavirus Attachment and Entry: Potential Sites for PML Therapeutics

Abstract: Purpose of review JC polyomavirus (JCPyV) is a significant human pathogen that causes an asymptomatic infection in the kidney in the majority of the population. In immunosuppressed individuals, the virus can become reactivated and spread to the brain, causing the fatal, demyelinating disease progressive multifocal leukoencephalopathy (PML). There are currently limited treatment options for this fatal disease. Attachment to receptors and entry into host cells are the initiating events in JCPyV infection and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 116 publications
(200 reference statements)
0
11
0
Order By: Relevance
“…JCPyV is widespread in the human population and largely presents as an asymptomatic kidney and B lymphocyte infection. However, within immunocompromised individuals, such as those previously infected with HIV or undergoing chemotherapy, JCPyV can spread to the CNS and cause PML, a severe demyelinating disease that frequently leads to death (5, 6). In the CNS, JCPyV primarily infects glia, including oligodendrocytes and astrocytes, as well as the cells of the choroid plexus, the latter a critical component of the blood-brain barrier (7).…”
Section: Commentarymentioning
confidence: 99%
“…JCPyV is widespread in the human population and largely presents as an asymptomatic kidney and B lymphocyte infection. However, within immunocompromised individuals, such as those previously infected with HIV or undergoing chemotherapy, JCPyV can spread to the CNS and cause PML, a severe demyelinating disease that frequently leads to death (5, 6). In the CNS, JCPyV primarily infects glia, including oligodendrocytes and astrocytes, as well as the cells of the choroid plexus, the latter a critical component of the blood-brain barrier (7).…”
Section: Commentarymentioning
confidence: 99%
“…In fact, studies have revealed that VP1-specific antibodies from PML patients cannot neutralize VP1 with PML-associated mutations unless subsequent steps in immune reconstitution are taken as well [40, 134]. These recent findings provide an enhanced understanding of JCPyV infection and PML development and suggest that a major area of novel PML therapeutics should focus on humanized mAbs that target PML-associated mutations, vaccines that provide VP1-specific immunity and protect from PML-associated mutation infections, in combination with treatments to boost the host immune system [40, 41, 136].…”
Section: Polyomavirusesmentioning
confidence: 99%
“…Moreover, a broadly-neutralizing antibody that recognizes a highly conserved fusion loop of ZIKV E can neutralize ZIKV in mouse models [243]. Additionally, recent studies to identify a treatment for JCPyV-induced PML demonstrates that the most promising candidates are mAbs that target viral capsid protein VP1 and vaccines that stimulate VP1-based immunity [41]. These treatments likely lead to neutralization of circulating virus and prevent JCPyV binding to receptors on host cells.…”
Section: Perspectivesmentioning
confidence: 99%
“…There lytic infection of glial cells can result in a fatal demyelinating disease termed progressive multifocal leukoencephalopathy (PML) 3 . Currently, there is no licensed vaccine for JCPyV and treatment options are limited and usually seek to address the underlying causes of immunosuppression 4 . Effective antiviral therapies against JCPyV are critical to improve the outcomes of patients suffering from PML.…”
Section: Introductionmentioning
confidence: 99%